KARAKTERISTIK MUTU MINYAK KELAPA TRADISIONAL PADA UKM SUKSES BERSAMA DENGAN METODE FERMENTASI - Rosdiani Azis; Moh. Fikri Pomalingo; Ingka Rizkyani Akolo (Jurnal Technopreneur (JTech), 2020)
ABSTRACT Sukses Bersama SMEs is one of the Small Medium Enterprises (SMEs) that is involved in processing coconut into traditional coconut oil, coconut is a commodity that is spread throughout Indonesia but consumption of oil derived from coconuts is still very lacking. Coconut oil produced is generally of low quality (fast rancid), in addition to oil produced in a turbid color and has a distinctive aroma (blondo aroma), this is caused by poor oil processing and relatively long processing times which are often where being complained by the people , therefore it is necessary to use the Fermentation method as a solution for traditional coconut oil processing which is more effective and efficient. Data analysis was performed using descriptive methods. This study aims to determine the quality of coconut oil produced from Sukses Bersama SMEs. The parameters measured in this study are peroxide numbers, free fatty acid numbers, saponification numbers, Iodic numbers and organoleptic properties which include color and aroma. The results showed that \ fermented oil from SMEs fulfilled the Indonesian National Standards namely Iod Numbers 8.14 mg jod / 100g, Nil peroxide Numbers mg oxygen / g, Oxygenation Numbers 264.37 mg KOH / g and Free fatty acids 0.17% and color as well as normal scents. Keywords: SMES,coconut,CoConut Oil,Fermentation,Fatty Acid